Usage of DNA Fingerprinting Technology to Check Sample Error and Contamination in Molecular Laboratories - Dahui Qin; Mark Forster; Shital M. Gandhi; Ratilal Akabari; Zhong Zheng; Janella Lal; Katherine Lovinger (Current Issues in Molecular Biology, 2022)
Sample identification error is a severe medical error in clinical molecular diagnostic laboratories, which can lead to reporting the wrong results for the patient involved. Sample contamination can also lead to incorrect test reports. Avoiding sample identification error and sample contamination could be life-saving. Sample switch and sample contamination could happen on laboratory bench works, especially when pipetting into multi-well plates. It is difficult to realize such errors during laboratory bench work. Laboratory staff may not be aware of such an error when it happens. DNA fingerprinting technology can be used to determine sample identity and subsequently identify sample switch and sample contamination in the laboratory. Our laboratory has explored the usage of this technology in our quality control process and successfully established that DNA fingerprinting can be used to monitor sample switch and sample contamination in next-generation sequencing and BCR/ABL1 real-time PCR bench work.